“Pachamamista” Discourses versus Development Policies: The Debate over Sumak Kawsay in the Andes - Andreu Viola Recasens (Íconos)
In this article, a critical review is presented in terms of the proposal for sumac kawsay, suma qamaña, or good living (buen vivir), highlighting its conceptual indefinition, the idealized conception of Andean rural world in which it seems to be inspired and its of coherence with the macroeconomic policies promoted to-date by the Bolivian and Ecuadorian governments.